Competitive Repression of the artPIQM Operon for Arginine and Ornithine Transport by Arginine Repressor and Leucine-Responsive Regulatory Protein in Escherichia coli - Torres Montaguth, Oscar E.; Bervoets, Indra; Peeters, Eveline; Charlier, Daniel (Frontiers in Microbiology, 2019)
Two out of the three major uptake systems for arginine in E. coli are encoded by the artJ-artPIQM gene cluster. ArtJ is the high-affinity periplasmic arginine-specific binding protein (ArgBP-I), whereas artI encodes the arginine and ornithine periplasmic binding protein (AO). Both ArtJ and ArtI are supposed to combine with the inner membrane associated ArtQMP2 transport complex of the ABC-type (ATP-Binding Cassette). Transcription of artJ is repressed by ArgR (arginine repressor), the artPIQM operon is regulated by the transcriptional regulators ArgR and Lrp (Leucine-responsive regulatory protein). Whereas repression by ArgR requires arginine as corepressor, repression of PartP by Lrp is partially counteracted by leucine, its major effector molecule. We demonstrate that binding of dimeric Lrp to the artP control region generates four complexes with a distinct migration velocity, and that leucine has an effect on both global binding affinity and cooperativity in the binding. We identify the binding sites for Lrp in the artP control region, reveal interferences in the binding of ArgR and Lrp in vitro and demonstrate that the two transcription factors act as competitive repressors in vivo, each one being a more potent regulator in the absence of the other. This competitive behavior may be explained by the partial steric overlap of their respective binding sites. Furthermore, we demonstrate ArgR binding to an unusual position in the lrp control region, downstream of the transcription initiation site. From this unusual position for an ArgR-specific operator, ArgR has little direct effect on lrp expression, but interferes with the negative leucine-sensitive autoregulation exerted by Lrp. Direct arginine and ArgR-dependent repression of lrp could be observed with a 25-bp deletion mutant, in which the ArgR binding site was artificially moved to a position immediately downstream of the lrp transcription initiation site. This finding is reminiscent of a previous observation made for the carAB operon encoding carbamoylphosphate synthase, where ArgR bound in overlap with the downstream promoter P2 does not block transcription initiated 67 bp upstream at the P1 promoter, and further supports the hypothesis that ArgR does not act as an efficient roadblock.